2019
DOI: 10.1016/j.learninstruc.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Small-group collaboration and individual knowledge acquisition: The processes of growth during adolescence and early adulthood

Abstract: Research into small-group collaboration during middle to late childhood shows that while individual understanding can be promoted through exchanging differing opinions, the joint analyses that groups construct while collaborating play a tangential role. Individuals may or may not accept these constructions depending upon processes of reflection and reconciliation that are triggered through difference and sometimes occur post-group. Recognizing a dearth of research with older participants (together with inconcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
2
24
0
2
Order By: Relevance
“…Coordination of joint work was evident in the interactions in which the students attended to the details of their creative work, managed and controlled the use of tools and materials, and followed the overall processes of their design and making activity (Table 1, rows 1-5). Our findings are consistent with previous research which has identified coordination as a pivotal part of collaboration (Li et al 2007;Hennessy and Murphy 1999;Howe and Zachariou 2019;Sun et al 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Coordination of joint work was evident in the interactions in which the students attended to the details of their creative work, managed and controlled the use of tools and materials, and followed the overall processes of their design and making activity (Table 1, rows 1-5). Our findings are consistent with previous research which has identified coordination as a pivotal part of collaboration (Li et al 2007;Hennessy and Murphy 1999;Howe and Zachariou 2019;Sun et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Previous research on students' creative collaboration in nonmakerspace settings show that students co-construct knowledge and understanding, create new understandings and ways of thinking (Miell and Littleton 2004;Rojas-Drummond et al 2014. Moreover, in creative tasks students need to coordinate their work, make joint decisions to construct and modify solutions, and support each other's work through dialog and action (Hennessy and Murphy 1999;Howe and Zachariou 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that learning science is to develop a scientific way of thinking that is characterized by question‐driven processes of inquiry about social and natural phenomena, in which evidence is gathered and alternative interpretations evaluated through a rational process that unfolds in discourse, leading to knowledge construction and conceptual understanding (see Driver et al., ; Jiménez‐Aleixandre & Erduran, ; Mortimer & Scott, ; Osborne et al., ). In fact, there is compelling evidence to show that the use of argumentation during peer interaction and, in particular, the discussion of different perspectives have an effect on students’ scientific content knowledge at different ages (Asterhan & Schwarz, ; Aydeniz & Dogan, ; Chen & She, ; Howe, ; Howe & Zachariou, ; Kaya, ).…”
Section: Introductionmentioning
confidence: 99%
“…Again, experimental evidence contradicts this hypothesis. Evidence has shown that the outcomes of group discussions are not related to individual gains in scientific understanding (Howe, ; Howe & Zachariou, ; Mugny & Doise, ; Sampson & Clark, ). Thus, group‐work argumentation leads to scientific content learning, not through the appropriation of correct group solutions or better ideas, but rather through individual cognitive processes that are triggered by discussion, especially when contradictions remain unresolved (Howe, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Piagetian position has been questioned, as mere exposure to disagreement has not been shown to be sufficient to result in conceptual gains (Asterhan & Swartz, 2007). Similarly, the notion that individuals make gains by appropriating enhanced solutions produced through group discussions has not been upheld (Howe & Zachariou, ). The current view is that individual cognitive processes are triggered by unresolved contradictions, particularly when the group strive to reach an agreement, but the argument is not resolved.…”
mentioning
confidence: 99%